DETERMINANT OF FRAUD IN GOVERNMENT AGENCY: EMPIRICAL STUDY AT THE FINANCE AND DEVELOPMENT SUPERVISORY AGENCY (BPKP) OF JAKARTA REPRESENTATIVE OFFICE - Barry Aditya Permana; Halim Dedy Perdana; Lulus Kurniasih (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTThe purpose of this study is to examine the influence of the appropriateness of compensation, the effectiveness of internal control systems and the organizational ethical culture on fraud in government agency. The dependent variable used in this study is fraud in government agency, while the independent variables used are the appropriateness of compensation, the effectiveness of internal control systems, and the organizational ethical culture. This study uses a sample of 105 respondents at BPKP Jakarta Representative Office. Sampling technique is conducted using convenience sampling method. Data analysis method used is multiple linear regression statistical analysis. Results of regression analysis show that the appropriateness of compensation has positive effect on the occurrence of fraud in government agency, the effectiveness of internal control system has negative effect on fraud in government agency, and the organizational ethical culture has no significant effect on fraud in government agency.